LESS land_more space Designing virtual space for architectural education and practice (EAAE Annual Conference Proceedings, 2024)
The topic “Architecture and urban spaces” is totally absent from the list of peer review evaluation panels of the European Research Council (ERC). “Architec- ture” appears twice, the first mention associated with civil engineering and the second understood as “Computer Architecture” in the Panel with the evocative name “PE6_1 Computer architecture, pervasive computing, ubiquitous computing”.The observation that the digital world has its own Architecture is associated with the concept of ubiquity. It characterizes the digital network and apparently goes beyond the concept of (urban) space. The digital world, the net, does not cancel space, on the contrary – it transfers it into another dimension, making it usable in another way, allowing experiences of ubiquity. This so-called virtual space requires an architectural design of its spatial dimension which, if not urban, we should at least determine as a public, collective or shared dimension.The progressive dematerialization of the project process has led to a wide range and types of spaces for architectural design: online platforms, repositories, archives are comparable to contemporary design offices, libraries, galleries, meeting and conference rooms. How to design those spaces in order to make them more effective and collaborative?